The Idea of Social Epistemology and Naturalistic Dilemma - Rimkutė, Audronė (Problemos, 2003)
The article analyses how in one of the branches of naturalistic epistemology - social epistemology - rises and is solved the "naturalistic dilemma". Two leading conceptions of social epistemology are examined - the veritism of Alvin Goldman and the sociological naturalism of Steve Fuller. These conceptions are opposing classical epistemology and radical naturalism in maintaining that epistemology must be both naturalistic and normative. The article argues that the theories of such “weak” naturalism are inevitably methodologically inconsistent. The evolution of the approaches of both the social epistemologists demonstrates this. At first Goldman constructs his conception of the naturalistic-normative epistemology as a combination of two distinct forms of inquiry - conceptual and empirical analyses - and so disproves the basic claim of naturalism that epistemological questions may be replaced by psychological questions, because psychological questions hold all the content there is in epistemological questions. Afterward his approach evolves to the more methodologically consistent naturalism, but in so doing it loses its normativity in the sense of classical epistemology. The initial idea of the sociological naturalism of Steve Fuller is epistemology as the "economy of text production". The epistemic norms are there only as the "technology" or "engineering" of the attainment of the available goals. So, at first Fuller chooses the first horn of the dilemma - naturalistic but not truly normative epistemology. Later, however, under the influence of the "scientific studies of science", Fuller switches to the fully philosophical conception of the science policy, where naturalism plays no greater role.